Relationship between trunk muscularity and club head speed in male golfers - Izumoto, Y.; Kurihara, T.; Maeo, S.; Sugiyama, T.; Kanehisa, H.; Isaka, T. (International Journal of Sports Medicine, 2020)
This study examined how the volume of trunk muscles and its bilateral asymmetry are related to club head speed in golfers. Fourteen right-handed male golfers performed five driver shots, and the club head speed for each trial was calculated from a three-dimensional reflective marker position of the club head immediately before impact. The volume of each side of the rectus abdominis, erector spinae, psoas major, quadratus lumborum, lateral abdominal wall muscle, and multifidus was determined using magnetic resonance imaging. For each muscle, the ratio of the larger to smaller side in muscle volume was calculated to assess bilateral asymmetry. The club head speed correlated positively with the volume of each side of the rectus abdominis and erector spinae, left quadratus lumborum, and the asymmetric ratio of the psoas major (r=0.595-0.747), but negatively with the asymmetric ratio of the quadratus lumborum (r=-0.641). Multiple regression analysis revealed that the right erector spinae volume and the asymmetric ratio of the psoas major were significant contributors for the club head speed (R2=0.797). These results indicate that the variation in the club head speed can be strongly explained by the absolute volume and bilateral asymmetry of specific trunk muscles.